Collaborative Ministry in Rural Areas. (2nd July 2016) - Burgess, Neil
Abstract : This article sets out to explore some significant questions around the practice of ministry in rural multi-parish benefices and particularly around the fostering and development of collaborative approaches to ministry. It argues that both historical factors and also an empathetic understanding of how full-time paid clergy see the nature of their calling are needed to balance what otherwise can seem to be an essentially pragmatic and utilitarian approach to the issues. It also raises questions about the assumptions built into recent Church of England reports on developing churches.